EDITORIAL - Vongurai, Rawin (Scholar: Human Sciences, 2023)
The Scholar: Human Sciences, a journal encompassing the fields of humanities and social sciences, has earned acclaim in the Thailand Citation Index (TCI) as a prominent publication since 2015. It currently holds the esteemed TCI: TIER2 classification. We take great pride in presenting the latest issue, Scholar: Human Sciences Vol. 15 No. 1 (January – June 2023), which features a collection of manuscripts that have undergone rigorous evaluation. Each submission has been meticulously reviewed through a blinded review process by three specialized reviewers from different institutions, both internal and external to the authors. This peer-reviewed accreditation ensures the scholarly quality and integrity of the published articles. This issue covers twenty-six articles. The first article titled “Influencing Factors of Behavior Intention of Master of Arts Students Towards Online Education in Chengdu Public Universities, China” aims to investigate influencing factors of behavioral intentions to use online education of Master of Arts students from three public universities in the Chengdu region of China. The second article titled “Determinants of Behavioral Intention to Use Hybrid Education Among Painting Students in Public Universities in Chengdu, China” aims to examine determinants of behavioral intention to use hybrid education among undergraduate students, majoring in painting at three public universities in Chengdu, China. The third article titled “The Application of UTAUT on eLearning Usage Among Physics Students of International Schools in Bangkok, Thailand” aims to identify factors impacting the behavioral intention and use behavior of eLearning among the high school students who have been studying physics in the final two years (Grade 11 and 12) of international schools in Bangkok, Thailand. The fourth article titled “The Influencing Factors of Gen Y Consumers' Purchase Intention of 3D Cameras in Mianyang, China” aims to examine relationship between social influence, perceived quality, attitude, satisfaction, and trust that influence purchase intention of 3D cameras of Generation Y customers in Mianyang, China. The fifth articled titled “The Assessment of Liberal Arts Students’ Behavioral Intention and Use Behavior of Mobile Video Apps in Chongqing, China” aims to assess the influencing factors of behavioral intention and use behavior towards mobile video apps, using a case of Gen Z students in liberal arts in Chongqing, China. The sixth article titled “A Study of Non-Resident Gen Y Chinese’s Purchase Intention of Real Estate in Panzhihua, China” aims to investigate the factors influencing the purchase intention of non-resident Gen Y Chinese of real estate in Panzhihua, China. The seventh article titled “Impacting Factors of Student Satisfaction and Loyalty: A Case Study of Private Universities in Zhejiang, China” mainly studies the factors impacting student satisfaction and loyalty of private universities in Zhejiang, China. The eighth article titled “Identifying Factors Influencing Continuance Intention and Actual Behavior of Online Computer Games in Chongqing, China” aims to identify the factors influencing students’ continuance intention and actual behavior of online computer games in Chongqing, China. The ninth article titled “Factors Impacting Student’s Behavioral Intention to Use Social Media Applications for Online Learning” aims to investigate the impacting factors of students’ behavioral intention to use social media applications for online learning. The tenth article titled “Behavioral Intention and Use Behavior of University Students in Chengdu in Using Virtual Reality Technology for Learning” aims to investigate the factors that influence the usage of virtual reality (VR) technology in learning among university students in Chengdu, China. The eleventh article titled “Factors Influencing Behavioral Intention of Online Learning in the Post-Covid Pandemic: A Case Study of a Primary School in Chengdu, China” aims to determine influencing factors of primary school students’ behavioral intention to use online learning in the post-Covid pandemic in Chengdu, China. The twelfth article titled “Examination of Tax Compliance Behavior Among Citizens in Phnom Penh, Cambodia” aims to examine drivers of tax compliance among citizens in Phnom Penh, Cambodia: economic compliance drivers, individual compliance drivers, subjective norms, perceived behavioral control, and perceived opportunity. The thirteenth article titled “Blended Learning in Teaching Piano Major Students in the Music Department of Hunan Vocational College of Art” aims to explore the effectiveness of the blended learning approach of piano on the performance of the major students in the Music department of Hunan Vocational College of Art and to determine the students' perceptions of the blended learning approach through a questionnaire survey. The fourteenth article titled “Behavioral Intention and Level of Usage on Convergence Media training Platform on Journalism University Students of Private Universities in Sichuan, China” aims to investigate the factors that affect students' behavioral intention and utilization of behavior in the convergence media training platform and to recommend cultivating converged media talents. The fifteenth article titled “Students’ behavioral intention on interactive video in primary Cinematography of Art Universities in Chengdu, China” aims to explore the effect of using interactive video in major cinematography classrooms and the acceptance of students. The sixteenth article titled “Factors Influencing Online Purchase Intention of Organic Food among Generation X Consumers in Ho Chi Minh” investigates factors influencing online purchase intention among Gen X consumers, incorporated reasons against organic food purchase, health consciousness, reasons for organic food consumption, attitudes, social influence, and perceived risk. The seventeenth article titled “Affecting Factors Affecting Non-Residents’ Attitude towards Online Purchase Intention in Taiyuan China” examines affecting factors of non-residents’ attitudes toward online purchase intention in Taiyuan, Shanxi Province, China. The eighteenth article titled “Switching Intention and Intention to Use Personal Cloud Storage Services Among Chinese Undergraduates” investigates the factors influencing Hangzhou undergraduates' switching intentions and intention to use personal cloud storage services. The nineteenth article titled “Understanding Online Shopping Behaviors and Purchase Intentions Amongst Undergraduate Students in Chengdu, China” focuses on the factors impacting purchase intention towards actual behavior amongst college students in Chengdu, Sichuan, China. The twentieth article titled “The Exploration on Satisfaction and Loyalty: A Case of Non-Teacher Training Major Students in Chuxiong Normal University, China” aims to examine the factors impacting student satisfaction and loyalty, using a case of non-teacher training major students at Chuxiong Normal University, China. The twenty-first article titled “Mobile Game Players’ Behavioral Intention to Use Facial Recognition Login System in Shanghai, China” aims to study the influences of perceived effectiveness of privacy policy, perceived privacy risk, perceived privacy self-efficacy, privacy concern, perceived usefulness, perceived ease of use, and the behavioral intention of mobile game players toward facial recognition login systems. The twenty-second article titled “Determinants of Postgraduate Students of Fine Arts’ Satisfaction and Performance of e-Learning in Chengdu Region of China” aims to investigate the determinants of e-learning satisfaction and performance of fine arts’ postgraduate students in five universities in Chengdu, China. The twenty-third article titled “Customer Loyalty in the Retail Industry in Yangon, Myanmar” aims to investigate the factors impacting customer loyalty in the retail industry in Yangon, Myanmar, which organizations and marketers need to focus on a competitive edge to gain sustainability in customer loyalty. The twenty-fourth article titled “Factors Affecting Satisfaction and Loyalty of Social Science Students in A Public University in Shanxi, China” aims to determine the impacting factors of satisfaction and loyalty among students majoring in social science at public universities in Shanxi Province. The twenty-fifth article titled “The Examination of Customer’s Brand Loyalty Toward Five-Star Hotels in Bangkok” aims to examine the causal relationship between advanced information and communication technology (ICT), perceived quality (tangibility, responsiveness, reliability, assurance, and empathy), brand awareness, brand image, and brand loyalty. The twenty-sixth article titled “Key Influencers of Satisfaction and Behavioral Intention of In-patients in Chengdu, China” aims to evaluate key influencers of satisfaction and behavioral intention of In-patients in Chengdu, China, which the hospital can understand the expectations of in-patients and improve competitiveness.